MANAGEMENT OF HYPERPROLACTINEMIA CAUSED PITUITARY MICROADENOMA - Ibnu Muttaqin; Haviz Yuad (Universitas Andalas, 2024)
Hyperprolactinemia is an increase in fasting levels of the hormone prolactin above 20 ng/ml in menand above 25 ng/ml in women. Hyperprolactinemia occurs more often in women of reproductive age,with a percentage of 9 – 17%. The etiology of hyperprolactinemia can occur due to abnormal pituitarysecretions, systemic disease, use of drugs, damage to the hypothalamus-pituitary axis. A 33-year oldfemale patient came to the FER Polyclinic at M. Djamil Hospital with complaints of not menstruatingfor the past 2 months. Irregular menstruation since 15 years ago, menstruation 2-3 times in 6 months,irregular cycle for 7-8 days. The patient also complained of a fluid like breast milk coming out of thebreast for 5 years, initially the fluid came out in a trickle and then gradually reduced and now the fluidcomes out occasionally if the breast is squeezed. From the supporting examinations carried out, it wasfound that the prolactin hormone level in this patient was 134.53, and the results of the MRIexamination showed a mass measuring 1.05x1.12x0.5 mm, which was diagnosed as secondaryamenorrhea, hyperprolactinemia, and suspected pituitary microadenoma. The patient will bemonitored for general condition and vital signs, as well as consultations with colleagues involved, suchas consultations to the Internal Medicine section, Endocrinology, Metabolic and Diabetes Subdivision.